Urban Road Pricing: Public and Political Acceptability. - Whittles, Martin J. (Taylor and Francis, 2017)
"Title first published in 2003. As more and more cities consider introducing urban road pricing schemes, this book describes, compares and contrasts arguments for and against using this transport policy instrument. It investigates the acceptability of various forms of road pricing schemes by examining and contextualising actual schemes and hypothetical scenarios. The resulting analysis provides a sociological theory of acceptability, carefully grounded in arguments about road pricing, which demonstrates how professional discourses diverge from publicly acceptable arguments. It also suggests ways in which consensus can be reached between the various road pricing options."--Provided by publisher.